Students’ Thought Process in Solving Inverse Proportion Problem in Terms of Cognitive Style and Gender Based on Information Processing Theory - Rusmin R. M. Saleh; Tasanif Nurlaila H.; Triyono Ageng (Jurnal Pedagogi dan Pembelajaran, 2025)
Students’ ability to solve inverse proportion problems remains low due to difficulties in understanding variable relationships, indicating differences in thinking processes related to cognitive styles and gender. This study aimed to analyze, compare, and evaluate students’ thinking processes in solving inverse proportion problems based on cognitive style and gender using an information-processing theoretical framework. This research employed a qualitative approach with a descriptive-exploratory design. The research subjects consisted of eight eighth-grade students selected purposively, representing Field Independent (FI) and Field Dependent (FD) cognitive styles as well as male and female students. Data were collected through written mathematical problem-solving tests and in-depth interviews as the main research instruments. The data were analyzed using interactive qualitative data analysis. The findings revealed that differences in students’ thinking processes were more strongly influenced by cognitive style than by gender, in line with the primary objective of the study. FI students tended to apply systematic and analytical strategies, were able to filter relevant information, and independently verify their answers, whereas FD students relied more on intuitive strategies, required more time to understand the problems, and were more dependent on external context. Overall, this study concludes that cognitive style is a key factor in determining the quality of students’ mathematical thinking processes. The implications of this study highlight the importance of early identification of students’ cognitive styles and the development of adaptive instructional models.